PENGARUH RASIO HUTANG, PROFIT MARGIN, UKURAN PERUSAHAAN, DAN LIKUIDITAS TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN PROPERTI, REAL ESTATE, DAN KONSTRUKSI YANG TERDAFTAR DI BEI - Tan, James; Evelyn (MANAJEMEN DEWANTARA, 2023)
Financial distress is the stage where the company experiences a gradual and continuous decline in its financial condition, before the company goes bankrupt or goes into liquidation. The purpose of this study was to determine the effect of debt ratios, profit margins, firm size and liquidity on the company's financial distress. The population in this study were 75 property, real estate, and construction sector companies listed on the IDX in 2016-2021, which were obtained using the purposive sampling method. The data analysis method used in this study is the multiple linear regression method, which is applied using SPSS and eViews applications. The financial distress variable was measured using the Altman Z-Score method, the debt ratio variable was measured by the debt to asset ratio, the profit margin variable was measured by the net profit margin, the firm size variable was measured by looking at the company's total assets and the liquidity variable was measured using the current ratio. The type of data used in this study is primary data obtained from financial statements on the website of the related company and secondary data in the form of data from bloomberg.com. The results of this study indicate that company size, profit margin, and liquidity have a positive and significant effect on financial distress. While the debt ratio variable has a negative and significant effect on financial distress. This research is expected to be useful for readers who want to know what are the company's internal factors that influence the performance of companies in the property and real estate sector, and can use this research as a reference in conducting further research.size and liquidity have no significant effect on financial distress. This research is expected to be useful for readers who want to know what are the company's internal factors that affect the performance of the property and real estate sector companies, and can use this research as a reference in conducting further research.